PENGARUH PEMAHAMAN SISWA TENTANG CARA MENGINDEKS SURAT TERHADAP HASIL BELAJAR KEARSIPAN SISWA KELAS X SMK-2 NUR HASANAH MEDAN - Nurdiana Putri Sirait; Rijal Rijal (Jurnal Inovasi Penelitian, 2022)
This study aims to influence students' understanding of how to index letters on student archiving learning outcomes in class X SMK-2 Nur Hasanah Medan. The data obtained were analyzed by means of quantitative analysis to calculate the initial data on student learning outcomes, final data on student learning outcomes, and the average value of the results of students' understanding of how to index letters. The study consisted of 2 classes, namely class X-A OTKP and X-B OTKP with a total of 40 students. During this study, researchers have discovered the important influence of students' understanding of how to index letters on student archiving learning outcomes in the classroom. Researchers obtained the initial results of student learning 3216 and the final results of student learning were 3423. The results of the calculation of the hypothesis test showed that the value of t_(count) was 0.64 while the magnitude of t_(table) was at a significant level of 5% with dk = n-2 = 40-2= 38 is 1.68. Therefore, t_count t_table or 0.64 1.68. The data can be concluded that there is an influence on students' understanding of how to index letters on student learning outcomes. In the teaching process, especially in archival subjects.